Case Report: Linezolid-associated toxic optic neuropathy in patients with pulmonary tuberculosis: case series and mini review - Yun, Hee Jin; Kim, Su-Jin; Han, Kwang Eon; Choi, Eun Jung; Lee, Ji-Eun (Frontiers in Pharmacology, 2025)
Linezolid is a useful second-line medication for the treatment of tuberculosis that is resistant to multiple drugs. However, long-term therapy can cause side effects, such as optic neuropathy. We describe three cases of progressive painless bilateral visual loss in patients taking long-term linezolid therapy for multidrug-resistant and extensively drug-resistant tuberculosis. We reviewed the literatures and identified 58 cases of linezolid optic neuropathy. Discontinuation of linezolid resulted in a marked improvement in vision, however it was not complete in all patients. Knowledge of visual monitoring of patients undergoing long-term linezolid therapy is important for physicians and ophthalmologists.